Long-term monitoring of fish in a freshwater reservoir: Different ways of weighting complex spatial samples - Tesfaye, Gashaw C.; Souza, Allan T.; Bartoň, Daniel; Blabolil, Petr; Čech, Martin; Draštík, Vladislav; Frouzová, Jaroslava; Holubová, Michaela; Kočvara, Luboš; Kolařík, Tomáš; Martinez, Carlos; Moraes, Karlos R.; et al. (Frontiers in Environmental Science, 2022)
Anthropogenic activities continue to pose the greatest challenges to freshwater ecosystems. Therefore, long-term monitoring is essential for the management and conservation of these resources. Monitoring programs for freshwater bodies often use a range of indicators, including biological elements such as fish. Existing European standard provides a depth-stratified gillnet sampling approach mainly in benthic habitats and at the deepest part of lakes to account for the uneven distribution of fish. However, the commonly used CEN (European Committee for Standardization) protocol does not weight sufficiently habitat volumes and underrepresent pelagic habitats to calculate whole-lake catch and biomass per unit effort (CPUE and BPUE, respectively). Extended European standard gillnet (4 larger mesh-sizes added in the geometric series) catch data collected over 18 years (2004–2021) in Římov Reservoir (Czech Republic) were used for a method comparison on indices for relative abundance and biomass of fish: CEN protocol without volume-weighting and two volume-weighted approaches. We also evaluated changes in species composition and trends in these fish population over time. Results indicated interannual changes in species composition, relative abundance, and biomass of fish community. The CEN protocol tended to put greater emphasis on benthic habitats which generally have larger CPUE and BPUE. Consequently, the two volume-weighting approaches produced lower estimates of the two parameters, with the exception of the most dominant pelagic bleak Alburnus alburnus (L.). All approaches consistently showed an increasing trend in whole-reservoir fish abundance and a decreasing trend in biomass over the study period. Following our assessment, we put forward the volume-weighting approach that considers the Volume of the depth Stratum (VOST) for weighting as the most realistic approximation of fish populations and therefore recommend its use.